Molecular phylogenetics of mormolyca (orchidaceae: maxillariinae) based on combined molecular data sets - Arévalo, Rafael (Universidad de Costa Rica, 2013)
The Neotropical orchid genus Mormolyca Fenzl, as currently circumscribed, encompasses a diverse group of ca. 27species. Many of these were included traditionally in Maxillaria sect. Rufescens, when similarity of floral morphology was considered foremost in their classification rather than the evolutionary history of the taxa. In order to begin revising species delimitation and clarifying the evolution and biology of the genus, we present a phylogenetic hypothesis using sequence data from five plastid loci (rpoC1, matK gene and flanking trnK intron, atpB-rbcL intergenic spacer, and the 3’ portion of ycf1) and the nuclear ribosomal internal and external transcribed spacers (ITS, ETS). Resulting trees using both Bayesian and parsimony inference are congruent with each other, and generally well resolved. Based on current level of sampling across Maxillariinae, these molecular data support the monophyly of Mormolyca and shed light on the interspecific phylogenetic patterns within the genus. These include an early divergent paraphyletic grade of Mormolyca species successively sister to a clade with at least two definable subclades within. The latter are characterized by two different flower morphologies that are likely related to their pollination systems. Although not all relationships within the genus are fully resolved or supported, these results offer a first glimpse into the phylogeny of a small group of epiphytic orchids characterized by an unusually high level of variable vegetative characters, floral fragrance profiles, and pollination systems.